Implementation of Electric Vehicles in The Internal Route of The International University of Ecuador - Vladimir Azanza; Álvaro Remache; Soraya Ruiz; Gorky Reyes; Andrés Castillo (Universitas Diponegoro, 2021)
Sustainable campuses have become one of the main objectives of agendas for a wide range of universities as a result of the impacts generated by the activities carried out within an academic life and how they directly affect the environment. An important aspect of the educational model of the International University of Ecuador, considering education as a focal transforming point of collective change, is to teach values and responsibility for the environment, considering that in terms of sustainability a higher education should not be understood only from the technical point of view, but as a process of realizing the significance of substantial values that would encourage future professionals to commit to the construction of a more fair and equitable society. For this reason, the objective of this study is to analyze sustainability through the implementation of electric mass transport vehicles in the internal route of the International University of Ecuador, for which the methodology is based on a quantitative approach, whose type of study is exploratory and of an inductive-deductive nature, analyzing the variables that directly influence a sustainable environment such as altitude above sea level (geographical location), benefited people, consumption and routes. Instruments such as sampling and surveys will be used to determine the decrease in polluting emissions that can affect the natural environment of the area. The technical considerations are the following: the location of the campus presents average slopes of 7.76 ° at 2560 masl, the results of autonomy in a route are 14.8 km benefiting around 450 people a day from the university community, having an annual load consumption of 297311 KWh during day hours and of 114715 KWh during night hours. With the implementation of an electric vehicle for the internal route, a power of 154.7 KW is required to overcome a slope of 18 ° with a campus route of 178.4 km, with this it would stop emitting 29.6 tons of CO2 and 0.76 tons of gases harmful for the environment per year